Medical Education: Traditional System vs. Integrated System - Haque, Anwar Ul (International Journal of Pathology, 2018)
There are many institutions where education is still impartedin traditional pedagogy style! There is subject oriented lecturingwithout integration with other subjects, clinical correlationsand clinical scenarios. The student is often lostamidst encyclopaedic facts! Even learning objectives are notprovided! The major emphasis had been on passing the examinationsrather than acquiring useful knowledge andlearning the skills! Without knowing the usefulness of theobjectives and relevance to real life, the student if oftenbored and looses attention and concentration. There is nospark and motivation for research. Many such flaws andinadequacies of this system were realized and hence integratedsystem of education with horizontal and vertical integrationof the subjects was introduced! Integrations is naturaljust like an embryo with simultaneous coordinatedgrowth of all organ systems! The integration makes "dullboring subjects" meaningful and interesting as it instils thepurpose of learning!